Pengaruh Pengawasan Terhadap Produktivitas Kerja Karyawan - Setiawati, Aprilia; Setiawardani, Maya (POLITEKNIK NEGERI BANDUNG, 2016)
PT Matahari Department Store Tbk is a company engaged in selling retail fashion’s apparel. One of the management’s functions performed in Matahari Department Store Bandung Indah Plaza is controlling function. By the area of 5700m2 and a large number of employees, it’s such an obstacle for the supervisor/coordinator to oversee every employee. So many employees are not doing a good job. This issue caused fluctuations in employee productivity from July to December 2013. Therefore, this study aims to determine the level of controlling, employee productivity levels and influence levels between controlling and employee productivity in Matahari Department Store Bandung Indah Plaza. The population in this study consisted of an employee which are permanent employees and suppliers of amount 498 people, with a research sample of 120 employees. In this study, the method of analysis used is descriptive analysis, correlation and simple linear regression. According to this study result, controlling and employee productivity is at a good level. Controlling contribute to affect employee work productivity by 16,5% obtained from the coefficient of determination, while 83.5% were influenced by the contributions of other factors which is not explained in this research. The correlation value of 0.407 indicates a moderate relationship between controlling and employee productivity.